Women's empowerment, extended families and male migration in Nepal: Insights from mixed methods analysis - Doss, Cheryl R.; Meinzen-Dick, Ruth S.; Pereira, Audrey; Pradhan, Rajendra (Elsevier, 2022)
Highlights •Combining qualitative and quantitative methods sheds new light on women's empowerment processes. •Upper caste Nepali women are disempowered by patriarchy; lower caste women by poverty and patriarchy. •Non-migrant husbands mediate the disempowering effects of living with in-laws. •Control over time, not just hours worked, is an important component of empowerment.